Pengendalian Kualitas Produksi Sandal Japit Pada CV. Aluna Berdasarkan Metode Failure Mode And Analys (FMEA) - Agung Setia Budi; Misbach Munir (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
CV ALUNA is a company engaged in the production of flip-flops. In its production process, the company faces various defects that may affect product quality and corporate reputation. This research aims to analyze and improve the quality of flip-flop products using the Failure Mode and Effect Analysis (FMEA) method. FMEA is used to identify failure modes, determine the values of Severity (S), Occurrence (O), and Detection (D), and calculate the Risk Priority Number (RPN) for each type of failure. The results indicate that the three main processes with the highest RPN values are cutting, printing, and sanding. The highest RPN value is found in the cutting process at 512, followed by printing and sanding processes, each with a score of 448. Based on these findings, improvement suggestions were proposed focusing on worker accuracy, equipment maintenance, and process supervision. The implementation of the FMEA method is expected to reduce production defects and significantly improve product quality at CV ALUNA. Keywords: CV.ALUNA;  FMEA; Flip-Flops; Product Quality; RPN